Current state of the problem and results of ex vivo perfusion of donor hearts - M. O. Zhulkov; A. V. Fomichev; S. A. Alsov; E. N. Cleaver; A. M. Chernyavsky (Вестник трансплантологии и искусственных органов, 2020)
Patients with drug refractory end-stage heart failure fall into the severe category of cardiological patients. Numerous studies have shown the superior efficacy of heart transplantation over other treatments for end-stage chronic heart failure. However, despite decades of achievements in transplantology, shortage of donor organs remains a pressing and unresolved issue. The only way to reduce shortage of donor organs is to use donors with advanced criteria, which requires the use of latest technologies in organ resuscitation and conditioning.